1991
DOI: 10.1037/0022-3514.60.6.861
|View full text |Cite
|
Sign up to set email alerts
|

Attachment in marriage: Effects of security and accuracy of working models.

Abstract: Working models of attachment in marital functioning were examined. The security and accuracy of working models were measured with a new Q-sort method. Spouses with secure working models (self as relying on partner and partner as psychologically available) showed more constructive modulation of emotion and reported better marital adjustment. The accuracy of internal working models, measured with an objective index of spouses' agreement about models, was associated with independent reports of marital adjustment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
275
3
30

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(337 citation statements)
references
References 16 publications
25
275
3
30
Order By: Relevance
“…For example, Kobak and Hazan (1991) found that satisfied intimates held more accurate or convergent perceptions of their spouses' working models of attachment. To index accuracy (in terms of the relative ordering of attachment items), Kobak and Hazan computed the intracouple correlations between an individual's ratings of his or her partner on a variety of attachment dimensions and the partner's self-ratings.…”
Section: A Final Test Between Illusions and Understanding: Trait-specmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kobak and Hazan (1991) found that satisfied intimates held more accurate or convergent perceptions of their spouses' working models of attachment. To index accuracy (in terms of the relative ordering of attachment items), Kobak and Hazan computed the intracouple correlations between an individual's ratings of his or her partner on a variety of attachment dimensions and the partner's self-ratings.…”
Section: A Final Test Between Illusions and Understanding: Trait-specmentioning
confidence: 99%
“…Within an attachment theory framework, such generalized expectancies about others are thought to be rooted in individuals' early experiences with attachment figures and structure their later construals of their adult close relationships (e.g., Kobak & Hazan, 1991). However, consistent with our findings, adult children of divorce appear to have pessimistic expectations about others in general and the institution of marriage (i.e., general working models), but they are still hopeful and optimistic about the possibilities for their own romantic relationships (Carnelley & Janoff-Bulman, 1992).…”
Section: Maintaining Idealism: Models Of Self and Othermentioning
confidence: 99%
“…Despite the proliferation of studies examining the role of adult attachment styles in love relationships (e.g., CarneUey & Janoff-Bulman, 1992;Collins & Read, 1990;Feeney & NoUer, 1990;Hazan & Shaver, 1987Kobak & Hazan, 1991;Levy & Davis, 1988;Mikulincer & Erev, 1991) and interpersonal processes (e.g., Bartholomew & Horowitz, 1991;Mikulincer & Nachshon, 1991;Simpson, Rholes, & NeUigan, 1992), there has been relatively little work conducted examining the potential impact of attachment security on psychological distress and disorder in adulthood. This state of affairs is particularly surprising given both the well-documented association between insecure attachments in infancy and behavior problems (e.g., Sroufe, 1988) and theory linking internal working models (mental representations of the self and others) formed in infancy to adult psychological disturbance (Bowlby, 1980;Bretherton, 1987;Cummings & Cicchetti, 1990;Diamond & Blatt, 1994;Gotlib & Hammen, 1992).…”
Section: Attachment Security and Psychological Disturbancementioning
confidence: 99%
“…It plays a noticeable role in establishing new friendships and enhancing the level of SI. Studies reported a positive relationship between avoidant attachment and unwillingness to open disclosure (Collins & Read, 1990;Kobak & Hazan, 1991).…”
Section: Discussion and Recommendationsmentioning
confidence: 99%